LE POIDS DES COMPÉTENCES LINGUISTIQUES DANS LE MARCHÉ DE L’EMPLOI EN ALGÉRIE - Bachir Bessai (Studii de gramatică contrastivă)
This contribution aims to analyze the linguistic skills requirements for accessing the job market in Algeria. Based on a sample of 500 job offers, published on emploitic.com website, we review those that require linguistic proficiency in one or more languages. While not all recruitments necessarily go through job offers posted on this portal, this study nevertheless provides a broad spectrum of the requirements of the Algerian job market. To better explain the major statistical trends, we complemented this study with an interview conducted with a headhunter who has extensive knowledge of the business world in Algeria.